KINETIC BEHAVIOR IN THE HYDROGENATION OF FURFURAL OVER Ir CATALYSTS SUPPORTED ON TiO2 - HUGO ROJAS (Dyna, 2010)
The kinetics of the liquidphase hydrogenation of furfuraldehyde to furfuryl alcohol over Ir catalysts supported over TiO2 was studied in the temperature range of 323 to 373 K. The effect of furfural concentration, hydrogen pressure and the solvent effect were also studied. A high selectivity towards furfuryl alcohol was demonstrated. Initial rates describes the order global of the reaction. The experimental data could also be explained using the LangmuirHinshelwood model with of a singlesite with dissociative adsorption of hydrogen and the surface reaction as the ratecontrolling step provided the best fit of the experimental data.